Patterns of Consonant Clusters in Word Initial, Medial, and Final Positions in Yemeni Arabic - Jubran AL-Mamri, Muhammed (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2021)
Yemeni Arabic (YA) has a significant number of consonant clusters in word initial, medial, and final positions. However, their frequency of usage is not uniform. This study aims to investigate the patterns of consonant clusters in word initial, medial, and final positions in YA and also to find out the most and least frequent clusters in terms of their percentage. Qualitative and quantitative methods were used in data analysis in this study. All the words were analyzed using Statistical Package for Social Sciences (SPSS). There are features of consonant clusters in Yemeni Arabic which differ from Modern Standard Arabic and some other Arabic dialects. In Yemeni Arabic, there are 29 consonants and 10 vowels, 5 long and 5 short vowels. The maximum number of onset cluster is three (e.g. /∫tsu:q/ “she will drive” while coda cluster is two (e.g. /satˤħ/ “roof”). Furthermore, the maximum number of medial clusters are also two (e.g. /muχ.lsˤu/ “sincere”. The analysis undertaken will throw light on the frequency and percentages of the occurrences of the consonant clusters on the basis of a word list, which is justified with the help of statistical support.